THE ROLE OF EMOTIONAL INTELLIGENCE IN ENHANCING TEACHER-STUDENT RELATIONSHIPS IN RURAL SCHOOLS - Kasheem, Amaal; Baroud, Najah; Khamis Almajri, Sumaia (Penerbit Lafadz Jaya, 2025)
This study explores the role of Emotional Intelligence (EI) in enhancing teacher-student relationships in rural schools. It examines how teachers' emotional intelligence affects their interactions with students, the classroom environment, and overall student engagement and academic performance. Using a qualitative research design, the study collected data through semi-structured interviews and classroom observations with 20 teachers and 60 students from rural secondary schools. The findings reveal that teachers with high EI demonstrate stronger self-awareness, empathy, and emotional regulation, which foster positive teacher-student relationships and create emotionally supportive learning environments. Students of emotionally intelligent teachers reported feeling more engaged, confident, and academically motivated. However, the study also identified challenges faced by rural teachers, such as emotional burnout and lack of institutional support, which hindered their ability to fully apply their emotional intelligence. The study emphasizes the need for targeted professional development programs to enhance EI in teachers, especially in rural schools where socio-economic and emotional challenges are more pronounced. The results underline the importance of EI in promoting academic success and emotional well-being for students, highlighting the critical need for EI-focused teacher training to improve educational outcomes in rural settings.